Expanding Educational Frontiers in Neurosurgery: Current and Future Uses of Augmented Reality. Issue 2 (11th November 2022) - Olexa, Joshua; Cohen, Jonathan; Alexander, Tyler; Brown, Cole; Schwartzbauer, Gary; Woodworth, Graeme F.
Abstract : BACKGROUND: Augmented reality (AR) technology is a new and promising option to advance and expand neurosurgical training because of recent advances in computer vision technology, improved AR software and hardware, and growing acceptance of this technology in clinical practice. OBJECTIVE: To analyze the current status of AR use cases with the goal of envisioning future uses of AR in neurosurgical education. METHODS: Articles applying to AR technology use in neurosurgical education were identified using PubMed, Google Scholar, and Web of Science databases following the Preferred Reporting Items of Systematic Reviews and Meta-Analyses guidelines. Articles were included for review based on applicable content related to neurosurgical or neuroanatomy training. Assessment of literature quality was completed using standardized MERSQI scoring. RESULTS: The systematic search identified 2648 unique articles. Of these, 12 studies met inclusion criteria after extensive review. The average MERSQI score was 10.2 (SD: 1.7). The most common AR platform identified in this study was the Microsoft Hololens. The primary goals of the studies were to improve technical skills and approaches to surgical planning or improve understanding of neuroanatomy. CONCLUSION: Augmented reality has emerged as a promising training tool in neurosurgery. This is demonstrated in the wide range of cases in technical training and anatomic education. It remains unclear how AR-based training compares directly with traditional training methods; however, AR shows great promise in the ability to further enhance and innovate neurosurgical education and training.